A Bayesian's Bubble - LI, C. WEI; XUE, HUI (Journal of Finance, 2009)
The acceleration of the U.S. productivity growth in the late 1990s suggests a significant advance in technological innovation, making the perceived probability of entering a “new economy” ever increasing. Based on macroeconomic data, we identify a Bayesian investor's belief evolution when facing a possible structural break in the economy. We show that such belief evolution plays a significant role in explaining both the stock market boom and crash during 1998 to 2001. We conclude that a rational investor's uncertainty about the future of the U.S. economy provides an alternative explanation for the late 1990s stock market “bubble.”